Avaliação do potencial antifúngico e da citotoxicidade de derivados semissintéticos do eugenol - Dutra, Jessyca Aparecida Paes (2019)
The increase of resistant fungal infections directed the search for alternative strategies in order to identify new therapeutic approaches. Among these strategies is the molecular modification, which aims to obtain derivatives from synthetic or natural compounds. In the essential oil of clove is present eugenol, a phenolic with ample antifungal activity and structural patterns that favor the obtaining of analogues. In this context, the present study evaluated the antifungal and cytotoxic activity of eugenol analogues. The antifungal action was evaluated in vitro on Candida albicans and C. parapsilosis through minimal inhibitory (MIC) and minimal fungicide (CFM) concentration, and in silico on CYP51 by molecular docking. The evaluation of the morphological damage to the yeasts was performed through SEM. Basal and post-metabolic cytotoxicity were evaluated in vitro on cell lines by the MTT-tetrazolium test. In this study the derivatives 2 and 4, allyl chain present, presented greater antifungal action. However, derivatives 5 and 6 that undergo changes in the side chain showed activity similar to or less than eugenol. The evaluation of modes of interaction at the CYP51 site demonstrated that derivatives 2 and 4 have structural patterns essential for the interaction when compared to fluconazole. Both derivatives showed similar morphological changes to fluconazole, reinforcing the hypothesis of interaction with the active site of CYP51. These derivatives had baseline IC50 values of 34.57 and 14.60 μg/mL, respectively. Whereas 2 was less cytotoxic than amphotericin B, and more cytotoxic than fluconazole from 50μg/mL. Derivative 4 was more cytotoxic than both standards from 25μg/mL. However, after exposure to the S9 system, derivative 4 maintained cytotoxicity while 2 was more cytotoxic. Regarding the selectivity, derivative 2 showed higher SI for fungal cells when compared to 4 and eugenol. It was found that none of the analogs attended all desirable aspects. Some were more active while others presented reasonable cytotoxicity and varied profiles of selectivity and liver metabolism. In this way, it is concluded that derivatives 2 and 4 are attractive as prototypes for future antifungal drugs. However, directed changes should be based on the results obtained, in order to contribute to the expansion of the limited therapeutic arsenal with more active and less cytotoxic drugs